A systematic study on polymerization and photocatalytic performance by investigating Ag2O·x(MoO3) (x = 1, 2, 3, 4) photocatalysts. Issue 21 (5th October 2018) - Liu, Xintong; Li, Wenjun; Wang, Fangzhi; Li, Hongda; Ren, Chaojun; Zhao, Yanjun
Abstract : Polymerized Ag2 O· x (MoO3 ) samples showed superior photocatalytic performance, and polymerization could be a potential strategy to enhance the photocatalytic activity. Abstract : In this study, the relationship of polymerization and photocatalytic performance was systematically studied by investigating a series of Ag2 O· x (MoO3 ) ( x = 1, 2, 3, 4) samples. Characterization results indicated that two decisive factors of photocatalytic performance, light harvesting and the separation of charge carriers, were significantly influenced by polymerization. UV-vis diffuse reflectance spectra (DRS) illustrated that the visible light absorption range was significantly increased with the increase of polymerization degree. Photocurrent measurement showed that the separation of charge carriers increased until the polymerization degree increased to three, and further increase of polymerization degree restrained the separation of charge carriers because of the narrow band gap. The degradation experiment showed that the photocatalytic performance was significantly enhanced by polymerization, and the degradation rates of Ag2 Mo3 O10 and Ag2 Mo4 O13 reached a maximum and were nearly the same. Density functional theory (DFT) calculation was applied to explain the enhancement mechanism of light harvesting and photocurrent properties. This study strongly suggests that polymerization must be taken into account for design and exploitation of efficient photocatalysts.